INFORMATION TECHNOLOGY GOVERNANCE IN PUBLIC ORGANIZATIONS: IDENTIFYING MECHANISMS THAT MEET ITS GOALS WHILE RESPECTING PRINCIPLES (Journal of Information Systems and Technology Management, 2017)
The purpose of this article is to identify and validate a list of mechanisms that can meet the objectives and principles of IT Governance (ITG) in public organizations. These mechanisms can be useful to public organizations when implementing their ITG model. ITG mechanisms are a key part of an ITG model because high-level definitions (principles and objectives) are operationalized through them. This exploratory and descriptive cross-sectional research used qualitative and quantitative data. Data were collected in a literature review, structured interviews with ITG professionals and a survey with IT and Business Managers who belong to a network of managers, which is one of the main instances to discuss the ITG model. The results are a preliminary list of mechanisms identified through qualitative data and a final list of mechanisms validated through quantitative data. The focus is on public organizations because the necessity of an ITG model as a better means to govern the electronic services adoption in order to increase the public value to society.